EFFECT OF ASCORBIC ACID AND ALPHA TOCOPHEROL ON IMMUNE STATUS OF MALE SPRAGUE DAWLEY RATS EXPOSED TO CHRONIC RESTRAINT STRESS - Moazzam, Sadia; Hussain, M. Mazhar; Saleem, Shemaila (Journal of Ayub Medical College Abbottabad, 2012)
Background: The immune system provides protection against infectious diseases or other insults. Psychological stress may alter antibody production through neurobiological pathways. Antioxidant supplementation is thought to improve immune status and thereby reduce infectious morbidity. The aim of this study was to determine the preventive effect of ascorbic acid and alpha tocopherol on immune status of rats exposed to chronic restraint stress. Methods: A total of 150 healthy male Sprague Dawley rats were included in the study. They were divided into 5 groups, each comprised of 30 rats. Group I was the control group on normal diet. Group II rats were exposed to chronic restraint stress for 6 hours daily for 15 days, without antioxidant supplementation, whereas rats of groups III, IV and V were given supplementation of ascorbic acid or alpha tocopherol or both respectively, for one month prior to exposure of rats to chronic restraint stress. Total leukocyte count (TLC) and lymphocyte counts was done, and serum immuno-globulins (IgG, IgA, IgM, and IgE) levels were estimated using ELISA. Results: Total leukocyte and lymphocyte counts and serum IgA, IgE, IgG, and IgM levels were found significantly (pË‚0.001) decreased in rats exposed to chronic restraint stress compared to the rats not exposed to the restraint stress. The combined supplementation of ascorbic acid and alpha tocopherol significantly (pË‚0.001) prevented the decline in total leukocyte and lymphocyte counts and serum immuno-globulins compared to the administration of either of the two antioxidants. Conclusion: Antioxidants (ascorbic acid and alpha tocopherol) given in combination produce greater beneficial effect in improving the immune status of rats exposed to chronic stress than individual supplementation of either ascorbic acid or alpha tocopherol. Keywords: Stress, immune status, immuno-globulins, antioxidants, ascorbic acid, alpha tocopherol